2022
DOI: 10.1097/crd.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Cardiac Troponins in Patients With Chronic Kidney Disease

Abstract: Cardiovascular disease is a major cause of death worldwide especially in patients with chronic kidney disease (CKD). Troponin T and troponin I are cardiac biomarkers used not only to diagnose acute myocardial infarction (AMI) but also to prognosticate cardiovascular and all-cause mortality. The diagnosis of AMI in the CKD population is challenging because of their elevated troponins at baseline. The development of high-sensitivity cardiac troponins shortens the time needed to rule in and rule out AMI in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…The increase in troponin I levels in individuals with CKD is strongly associated with an increased risk of adverse cardiovascular events and higher overall mortality rates. Additionally, as CKD advances to more severe stages, the prognosis worsens (20) . Regarding YKL-40, this study showed a notable increase in HD patients with CVD compared to those without CVD and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in troponin I levels in individuals with CKD is strongly associated with an increased risk of adverse cardiovascular events and higher overall mortality rates. Additionally, as CKD advances to more severe stages, the prognosis worsens (20) . Regarding YKL-40, this study showed a notable increase in HD patients with CVD compared to those without CVD and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The additional important diagnostic advantage of highsensitive tests for immunochemical determination of cardiospecific troponins is the ability to determine cardiac myocytes damage at the subclinical level, which can be used to monitor and assess the prognosis of patients suffering from a number of chronic pathologies, including coronary heart disease [37], during the treatment of oncological diseases by using chemotherapeutic compounds, which are characterized by cardiotoxicity [38][39][40], as well as chronic obstructive pulmonary disease [41,42], chronic kidney disease [43,44], diabetes mellitus [45], arterial hypertension [46], etc.…”
Section: High-sensitive Cardiospecific Troponins: Characteristics Of ...mentioning
confidence: 99%
“…The additional important diagnostic advantage of high-sensitive tests for immunochemical determination of cardiospecific troponins is the ability to determine cardiac myocytes damage at the subclinical level, which can be used to monitor and assess the prognosis of patients suffering from a number of chronic pathologies, including coronary heart disease [ 32 ], during the treatment of oncological diseases by using chemotherapeutic compounds, which are characterized by cardiotoxicity [ 33 ], as well as chronic obstructive pulmonary disease [ 34 ], chronic kidney disease [ 35 ], diabetes mellitus (DM) [ 36 ], arterial hypertension [ 37 ], etc.…”
Section: High-sensitive Cardiospecific Troponins: Characteristics Of ...mentioning
confidence: 99%